2023
DOI: 10.1029/2023ja031828
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Solar Irradiation and Solar Wind Conditions on Heavy Ion Escape from Mars

Qi Zhang,
Mats Holmström,
Xiao‐dong Wang
et al.

Abstract: We apply a recently proposed method to estimate heavy ion escape from Mars. The method combines in situ observations with a hybrid plasma model, which treats ions as particles and electrons as a fluid. With this method, we investigate how solar upstream conditions, including solar extreme ultraviolet (EUV) radiation, solar wind dynamic pressure, and interplanetary magnetic field (IMF) strength and cone angle, affect the heavy ion loss. The results indicate that the heavy ion escape rate is greater in high EUV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The effects of IMF orientation, dynamic pressure, and the location of the Martian crustal field on magnetic reconnection on the dayside were studied by MHD numerical simulation (Wang et al 2022). Zhang et al (2023a) indicated that the highest ion escape rate corresponds to the solar wind being parallel to the IMF, while the lowest ion escape rate occurs when the solar wind is perpendicular to it. In our work, only IMF B z and V x exist, suggesting that the ion escape rate is relatively low compared to other solar wind conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of IMF orientation, dynamic pressure, and the location of the Martian crustal field on magnetic reconnection on the dayside were studied by MHD numerical simulation (Wang et al 2022). Zhang et al (2023a) indicated that the highest ion escape rate corresponds to the solar wind being parallel to the IMF, while the lowest ion escape rate occurs when the solar wind is perpendicular to it. In our work, only IMF B z and V x exist, suggesting that the ion escape rate is relatively low compared to other solar wind conditions.…”
Section: Introductionmentioning
confidence: 99%